2019
DOI: 10.1002/anie.201911356
|View full text |Cite
|
Sign up to set email alerts
|

Direct Mechanocatalysis: Palladium as Milling Media and Catalyst in the Mechanochemical Suzuki Polymerization

Abstract: The milling ball is the catalyst. We introduce a palladium‐catalyzed reaction inside a ball mill, which makes catalyst powders, ligands, and solvents obsolete. We present a facile and highly sustainable synthesis concept for palladium‐catalyzed C−C coupling reactions, exemplarily showcased for the Suzuki polymerization of 4‐bromo or 4‐iodophenylboronic acid giving poly(para‐phenylene). Surprisingly, we observe one of the highest degrees of polymerization (199) reported so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 54 publications
1
74
0
6
Order By: Relevance
“…[18] In our recentw ork ( Figure 1C) we first demonstrated that no ligands or salts are needed and pure palladium black was capable of catalyzing the reaction inside ab all mill. [9] In the next step we had palladium milling balls made and conducted the experiments inside az irconium vessel with said balls. By studying the conditions further, we made the following observations:1 .the reactioni sn ot proceeding in the absence of either palladium or base;2.the reaction is reaching completec onversion slower under directm echanocatalytic conditions compared to the palladium black or palladium salts.…”
Section: Càcc Oupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] In our recentw ork ( Figure 1C) we first demonstrated that no ligands or salts are needed and pure palladium black was capable of catalyzing the reaction inside ab all mill. [9] In the next step we had palladium milling balls made and conducted the experiments inside az irconium vessel with said balls. By studying the conditions further, we made the following observations:1 .the reactioni sn ot proceeding in the absence of either palladium or base;2.the reaction is reaching completec onversion slower under directm echanocatalytic conditions compared to the palladium black or palladium salts.…”
Section: Càcc Oupling Reactionsmentioning
confidence: 99%
“…Although, abrasion during millingc an be minimized due to wise selection of milling conditions, certain catalytic activity of the abraded species cannot be ruled out. [9] In ar ecent publication, our group conducted aP d-milling ball-catalyzedS uzukir eaction and exchanged the catalytically active milling balls against non-activeZ rO 2 balls after 4h of reaction. We observed that the rate of conversion decreaseda bruptly.T hat meanst hat Pd abrasion accumulating duringm illing is not the major active specie in this reaction and the Pd milling ball as well as their collisionsc ontributet ot he overall reaction.…”
Section: The Mechanismmentioning
confidence: 99%
“…18) Borchardt und Mitarbeiter stellten Poly(p-Phenylen) durch mechanochemische Suzuki-Kopplung dar, wobei hohe Polymerisationsgrade (bis zu 199) erreicht wurden und weder Lösungsmittel noch Liganden nötig sind. 19) Die Gruppe um Herres-Pawlis fand Ersatz für Zinn(II)oktanoat zur Laktidpolymerisation: Biokompatible Eisen(II)guanidin-Komplexe setzen kontrolliert 5000 Äquivalente des Monomers um. 20) Sie verwendeten das Monomer in technischer Qualität.…”
Section: Einblick: Polymere Und Nachhaltigkeitunclassified
“…So far, wide attention has been paid to the chemical conversion of CO 2 into high value-added energy, materials and chemical products. The beneficial use of CO 2 including the alternating copolymerization of CO 2 and epoxides to make degradable polycarbonates were popular ( Scheme 1 ), which is considered one of the most potential green polymerization processes [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In addition, polycarbonates have become important topics because of their environment-friendly properties, such as atom-economy, energy-saving and degradation, as well as their several biomedical and pharmaceutical applications [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the two metal centers could work cooperatively in propylene oxide (PO) and CO 2 copolymerization [ 37 , 38 ]. Nakano et al synthesized a series of dinuclear salen-Co catalysts [ 9 ] and proposed a bimetallic mechanism for the dinuclear catalyst in the absence of cocatalyst. Klaus and coworkers developed a dinuclear salen-Cr complex.…”
Section: Introductionmentioning
confidence: 99%